Evaluation of patient experience in county-level public hospitals in China: a multicentred, cross-sectional study - Lu Li; Rui Min; Chunyan Zi; Pengqian Fang; Biyan Wang; Changmin Tang (BMJ Open)
Objectives Patient experience is being widely considered in the evaluation of healthcare service quality, which is a key target for public hospitals under China’s New Healthcare Reform. This study aimed to illustrate patients’ experiences in county-level public hospitals, and identify aspects that need to be improved.Setting and participants Between 2016 and 2018, a cross-sectional study with 500 outpatients and 800 inpatients was conducted in 10 county-level public hospitals from Shandong Province, Hubei Province and Chongqing Municipality.Method A three-part questionnaire was used to evaluate patients’ experiences during their visits to hospitals. It comprised a questionnaire for basic information, the Picker Patient Experience (PPE-15) Questionnaire and the overall evaluation (a 3-point Likert scale to express patients’ satisfaction and patient loyalty). Patients’ experiences were classified according to six dimensions (information transmission and patient education, respect for patient preference, emotional support, physical comfort, involvement of family or friends and continuity of medical service). Both univariate and multivariate analyses were performed to evaluate patient experience.Results A total of 1241 valid questionnaires were analysed. The mean PPE-15 score was 41.33 (range, 23–56). The better the patient experience and satisfaction, the higher the patient loyalty (p<0.001). Except for hospital disparities, patients’ age and occupation status had a significant impact on patient experience (p<0.05). Of the six dimensions, the physical comfort score was the highest, while the respect for patient preference score was the lowest. Additionally, a strong correlation was found between the respect for patient preference dimension and patients’ overall satisfaction with their treatment experience.Conclusions Hospital managers and staff members should pay close attention to the preferences of patients and their families to improve patient experience.